INOVASI PEMBELAJARAN LINTAS DISIPLIN DALAM KERANGKA KURIKULUM MERDEKA DI SMAN 10 B0NE - Nur Hasdayanti; Muhammad Ali; Naila Kamila; Afdal; Nabila Putri; Muh. Alif; Zulfika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of interdisciplinary learning innovation within the framework of the Merdeka Curriculum at SMAN 10 BONE. Interdisciplinary learning is considered one of the relevant approaches in supporting the development of 21st-century competencies, such as critical thinking, creativity, collaboration, and communication. This study employed a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation involving teachers and students at SMAN 10 BONR. The results of the study indicate that the implementation of interdisciplinary learning was carried out through collaboration among subjects in the form of problem-based learning projects and Pancasila Student Profile Strengthening Projects. This learning innovation was able to increase student engagement in the learning process, strengthen problem-solving skills, and create more contextual and meaningful learning experiences. In addition, teachers acted as facilitators who encouraged students to actively explore various learning resources according to their interests and needs. However, the implementation of interdisciplinary learning still faced several obstacles, such as limited collaboration time among teachers and the readiness of supporting learning facilities. Therefore, strengthening coordination, teacher training, and school support are needed so that the implementation of interdisciplinary learning innovation can run optimally in supporting the success of the Merdeka Curriculum.